Social Capital and Community-Based Rural Tourism Development in Kauman Kidul, Salatiga, Central Java - Malinton Fauly; Pamerdi Giri Wiloso (FISIP Universitas Islam Negeri Raden Fatah Palembang, 2021)
This article aims to describe the role of social capital in the development of community-based tourism villages in Kauman Kidul, Salatiga City, Central Java Province, Indonesia. The research method used is qualitative with a case study approach. Data collection techniques used are in-depth interviews, observation, and document studies. Data processing uses triangulation to obtain valid and credible information. The key informant involved in this study was the Chair of the Sitalang Tourism Awareness Group. The results of this study indicate the role of social capital (norms, trust, and networks) that binds the social relations of the